PEACE-LOVE EDUCATION IN SURAH AL-HUJURAT VERSES 9-10 - Syamsu Nahar; Yusnaili Budianti; Dedi Nurniadi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
Peace is at the heart of the Quran and the essence of Islamic teachings. The Quran is quite realistic looking at humans. Because of the ego and its problems, it often forgets the value of peace so that social tensions between each other become a phenomenon that is not uncommon, even within the scope of the Muslim community itself. As a social being, man must follow specific provisions and rules if he lives and is in the midst of society. Islamic teachings have consistently called for peace in all corners of the world to invite people to peace.This study analyzes the urgency of peace-loving education in the Quran (Surah al-Hujurat Studies 9-10). This research uses a type of library research or library research with a content analysis or content analysis research approach, then collects data and draws conclusions from the research results.This study concluded that the urgency of peace-loving education in the Qur'an and in the study of surah al-Hujurat verses 9-10 states that the Quran has explained practical guidelines for managing peace. In QS al-Hujurat, verses 9 and 10 clearly explain that if two factions of believers dispute to the point of causing war, then it is incumbent upon Muslims to reconcile the two belligerent factions immediately. The life of modern, homogeneous, and global society today requires an understanding of the importance of mutual respect and respect for each other. Thus, peace is the goal of Islam, and the meaning of Islam is peace.